Competition of Politicians for Incentive Contracts and Elections - Hans Gersbach (Center for Economic Studies and ifo Institute (CESifo), 2001)
When politicians have lower discount factors than voters, democratic elections cannot sufficiently motivate politicians to undertake long-term socially beneficial projects. When politicians can offer incentive contracts which become effective upon reelection, the hierarchy of contracts and elections can alleviate such inefficient decision-making in politics. This mechanism still works if the public cannot commit itself to a reelection scheme or if the public is unsure about the politicians' time preferences. In the non-commitment case, incentive contracts may need to include a golden parachute clause.Keywords: Incentive contracts, politicians, long-term policies, elections and contracts, golden parachute clause
Keywords: 330; Incentive contracts; politicians; long-term policies; elections and contracts; golden parachute clause